Stereotactic body radiation therapy: A promising chance for oligometastatic breast cancer. (April 2016) - Scorsetti, Marta; Franceschini, Davide; De Rose, Fiorenza; Comito, Tiziana; Villa, Elisa; Iftode, Cristina; Navarria, Pierina; D'Agostino, Giuseppe Roberto; Masci, Giovanna; Torrisi, Rosalba; Testori, Alberto; Tinterri, Corrado; et al.
Abstract: Background: Multidisciplinary management of oligometastatic breast cancer with local therapy could improve disease control. The aim of our study is the assessment of safety and efficacy of Stereotactic Body Radiation Therapy (SBRT) in selected subset of patients. Patients and methods: Oligometastastic patients from breast cancer were treated with SBRT for 1–3 lung and liver lesions, in an observational study. Inclusion criteria were: age >18 years, ECOG 0-2, diagnosis of breast cancer, no extrapulmonary and/or extrahepatic disease, other metastatic sites stable or responding after chemotherapy were allowed, no life threatening conditions, less than 5 lung and liver lesions (with maximum diameter <5 cm), chemotherapy completed at least 3 weeks before treatment, written informed consent. Prescription dose ranged between 48 and 75 Gy in 3 or 4 consecutive fractions. Primary end-point was local control (LC). Secondary end-points were toxicity, overall survival (OS) and progression-free survival (PFS). Results: From April 2010 to June 2014, 33 patients for a total number of 43 lesions were irradiated. Median follow up was 24 months (range 3–59). Actuarial LC rates were 98% at 1 year and 90% at 2 and 3 years. Complete response, partial response and progressive disease were detected in 25 (53.2%), 16 (34%), and 6 (12.8%) lesions, respectively. Median OS was 48 months. Actuarial OS rates at 1 and 2 years were 93% and 66% respectively. Median PFS was 11 months, with a PFS rate at 1 and 2 years of 48% and 27%, respectively. At univariate analysis DFI >12 months, hormonal receptor positivity, medical therapies after SBRT showed a significant impact on OS. Treatment was well tolerated, with no G3-4 toxicities. Conclusions: SBRT is a safe and feasible alternative treatment of liver and lung oligometastases from breast cancer, in selected patients not amenable to surgery, with good local control and survival rate. Highlights: Oligometastatic breast cancer is a unique disease, amenable to local approaches. Local treatment for oligometastasis can increase local control and survival. Stereotactic body radiation therapy (SBRT) is valid local treatment. SBRT is well tolerated, with good local control and survival rates.